Corrosion protective properties of cellulose nanocrystals reinforced waterborne acrylate-based composite coating. (15th July 2019) - He, Yunjuan; Boluk, Yaman; Pan, Jinshan; Ahniyaz, Anwar; Deltin, Tomas; Claesson, Per M.
Highlights: The acrylate based waterborne coating shows good barrier performance during exposure to 0.1 M NaCl solution for 35 days. CNC can effectively reinforce the barrier performance of the matrix coating during long-term exposure. Interactions between matrix and CNC and its effect on the coating corrosion protection performance were elucidated. Abstract: The present investigation highlights corrosion protection of carbon steel by a waterborne acrylate-based matrix coating, with and without reinforcement by cellulose nanocrystals, by using electrochemical impedance spectroscopy in 0.1 M NaCl solution over a period of 35 days. Interactions between cellulose nanocrystals and the matrix coating were demonstrated by Fourier transform infrared spectroscopy. The results show that both coatings have high barrier performance but different protective characteristics during long-term exposure. The differences can be attributed to the reinforcement effect of cellulose nanocrystals caused by hydrogen bonding interactions between cellulose nanocrystals and the matrix coating.